ECO ENZYME PEMBERDAYAAN KELOMPOK PETANI DESA CIRANJANG CIANJUR TAHUN 2021 - Ishak Ramli; Yustina Peniyanti Jap (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2021)
This is a continuation PKM activity of the PKM carried out in 2016-2020. The PKM have successfully applied organik rice and developing financial institutions to help develop empowerment of farmers’ group in Jatinunggal, Sindangsari village, Ciranjang, Cianjur.West Java. Farmers 'income has increased, but this has not yet made young farmers' return to the village, considering that the increase has not been enough. First, because the farmers’ land is very small since it is distributed as inheritance. The second is it still a difficult and expensive organik fertilizer. In order to attract young human resources to increase their income, we introduced to manufacture, utilize and marketing eco enzyme products as organik fertilizers and as environmentally friendly organik cleaning products. We proposed producing and marketing eco enzyme as a solution to the income problem of the farmers group in Jatinunggal Sindangsari village, Ciranjang, Cianjur. One of the main benefits of this PKM activity is to give a solution to the rare and expensive organik fertilizer and increase understanding of the usefulness of eco enzyme products and market them in order to increase farmers' income. The implementation method is in collaboration with POKTAN in Jatinunggal, Sindangsari village, Ciranjang, Cianjur as a PKM partner through counseling and assistance in making Eco Enzyme, its benefits and how to market it. We have been doing the PKM activities from January to April 2021, in online meeting using WhatsApp group. As a result, in the first harvest POKTAN received additional income from saving organik fertilizer IDR 1,447,500 for one farmer and moreover they have additional income from selling Eco Enzyme products of IDR. 200,000. The total additional income is Rp. 1,647,500, and still they have inventory of 155 liters of Eco Enzyme productsABSTRAK:PKM ini merupakan kelanjutan dari PKM yang sudah dilakukan tahun 2016-2020. Kegiatan PKM sudah berhasil menerapkan padi organik dan Lembaga keuangan untuk membantu pengembangan pemberdayaan kelompok petani di Jatinunggal desa Sindangsari, Ciranjang, Cianjur. Pendapatan petani telah meningkat, namun hal ini belum membuat SDM muda petani kembali ke desa mengingat peningkatan belum mencukupi. Pertama karena tanah sawah milik sudah menjadi sangat kecil karena dibagikan sebagai warisan, kedua masih sulit dan mahalnya pupuk organik. Guna menarik minat SDM muda dalam menambah pendapatan mereka maka pengenalan, pembuatan, pemanfaatan, dan pemasaran produk eco enzyme sebagai pupuk organik dan sebagai produk pembersih organik ramah lingkungan, diusulkan sebagai solusi masalah pendapatan kelompok petani Jatinunggal desa Sindangsari, Ciranjang, Cianjur. Manfaat utama kegiatan PKM ini salah satunya adalah meningkatkan pemahaman kegunaan produk eco enzyme serta memasarkannya guna meningkatkan pendapatan petani.Metode pelaksanaan bekerja sama dengan POKTAN di Jatinunggal desa Sindangsari, Ciranjang, Cianjur sebagai mitra PKM melalui penyuluhan dan pendampingan pembuatan Eco Enzyme, manfaat serta bagaimana memasarkan nya. Kegiatan PKM secara daring pada Januari s/d April 2021. Hasilnya pada panen pertama POKTAN mendapatkan tambahan pendapatan dari penghematan pupuk organik dari satu petani sebesar Rp.1.447.500,- dan pendapatan dari penjualan produk Eco Enzyme sebesar Rp. 200.000, - Total tambahan pendapatan sebesar Rp. 1.647.500, - serta masih mempunyai persediaan produk Eco Enzyme sebanyak 155 l